Additive manufacturing of ceramic materials for energy applications: Road map and opportunities. Issue 7 (July 2022) - Cramer, Corson L.; Ionescu, Emanuel; Graczyk-Zajac, Magdalena; Nelson, Andrew T.; Katoh, Yutai; Haslam, Jeffery J.; Wondraczek, Lothar; Aguirre, Trevor G.; LeBlanc, Saniya; Wang, Hsin; Masoudi, Mansour; Tegeler, Ed; et al.
Abstract: Among engineering materials, ceramics are indispensable in energy applications such as batteries, capacitors, solar cells, smart glass, fuel cells and electrolyzers, nuclear power plants, thermoelectrics, thermoionics, carbon capture and storage, control of harmful emission from combustion engines, piezoelectrics, turbines and heat exchangers, among others. Advances in additive manufacturing (AM) offer new opportunities to fabricate these devices in geometries unachievable previously and may provide higher efficiencies and performance, all at lower costs. This article reviews the state of the art in ceramic materials for various energy applications. The focus of the review is on material selections, processing, and opportunities for AM technologies in energy related ceramic materials manufacturing. The aim of the article is to provide a roadmap for stakeholders such as industry, academia and funding agencies on research and development in additive manufacturing of ceramic materials toward more efficient, cost-effective, and reliable energy systems.